The Effect of Current Ratio and Total Assets Turnover on Stock Prices and Return On Assets as Intervening Variables - Heny Ratnaningtyas; Nurbaeti Nurbaeti (Islamic University of Kalimantan MAB Banjarmasin, 2023)
This study aims to determine the effect of the current ratio (CR) and total assets turnover (TAT) on stock prices and return on assets (ROA) as intervening variables in Hotels, Restaurants, and Tourism Companies during the Covid-19 Pandemic. This type of research is quantitative with a path analysis method using SmartPLS. The sampling technique used is saturated sampling because the population is the same as the sample, namely, ten companies listed on the Indonesia Stock Exchange. The results showed that: (1) The variables that have a significant effect on ROA are CR and TAT; (2) The variables that have a significant effect on stock prices are CR and ROA; (3) The variable that has no significant effect on stock prices is TAT; (4) The CR variable has a significant effect on stock prices through ROA; (5) The TAT variable has a significant effect on stock prices through ROA.